INNOVATIVE METHODS OF TEACHING GRAMMAR IN SECONDARY CLASSES (Western European Journal of Linguistics and Education, 2024)
This article focuses on exploring the effectiveness of teaching adverbs to 6th-grade pupils using graphic organizers. Adverbs play a crucial role in enhancing students' writing skills and language comprehension. The study aims to investigate the impact of graphic organizers as a teaching tool on the understanding, retention, and application of adverbs among 6th-grade students. Effective grammar instruction plays a crucial role in enabling students to develop strong language skills. However, traditional instructional methods often fail to engage and empower students, particularly in the context of teaching adverbs. This article aims to explore innovative methods for teaching grammar, with a specific focus on teaching adverbs, utilizing graphic organizers as a visual tool. By implementing these innovative techniques, educators can enhance student engagement, comprehension, and retention of grammatical concepts, ultimately fostering more effective language acquisition in 6th grade pupils